Posted by **Robert** on Tuesday, November 20, 2012 at 11:37am.

What value completes the square for the expression? x2 + 14x

Use the quadratic formula to solve the equation. x2 – 7x – 6 = 0

Simplify the expression. (–2i)(8i)

What are the solutions?

1/2x^2 + 2x + 3 =0

I need help

- Algebra 2 help!!! -
**mathfailure**, Tuesday, November 20, 2012 at 11:45am
for number one we see that this could be of the form (x+7)^2 so we expand to get x^2+14x+49 so we need to add 49

for number 2 we can just use the easy way (factoring) although you can use the quad formula. (x-1)(x-6) to get x=1,6

we multiply coefficients pretending i is a variable. so we get -16 i^2. we know i is the square root of -1 so i^2 = -1. Thus -16 i^2 = 16.

for the last one, multiply both sides by 2x^2 to get 1+2x^3+6x^2. Then we can let y=x^2. Thus we get 1+2y^2+6y and we rearrange terms to get 2y^2+6y+1.

through the quadratic formula etc. we get a complicated non-real answer: x= (-4+2i\sqrt2)/2, (-4-2i\sqrt2)/2

## Answer This Question

## Related Questions

- math - (4.35E-2 - x)(7.56E-2 -x ) ============================ (0.324 + 2x)2 ...
- math - Heather is solving an equation by graphing the expressions on both sides...
- Algebra 2 Help - 1.) Solve for x. 2x(x - 12) = -40 2.) Solve for x. 3x2 + 2x = ...
- Algebra 2 - 1.) Solve for x. 2x(x - 12) = -40 2.) Solve for x. 3x2 + 2x = 12 - ...
- Algebra - Bob thanks for answering my question, it still seems a tad bit ...
- math algebra - Factor the given expression. Then use the zero product rule and ...
- math algebra - Factor the given expression. Then use the zero product rule and ...
- math algebra - Factor the given expression. Then use the zero product rule and ...
- math - is these answers correct? solve the equation: 2x^2 +8x - 17=(x +2)^2= x=-...
- Pre- Algebra - 1. What is (-7)^5 in expanded form? 2. Simplify the expression...

More Related Questions